Aptamers against Cells Overexpressing Glypican 3 from Expanded Genetic Systems Combined with Cell Engineering and Laboratory Evolution. (7th September 2016) - Zhang, Liqin; Yang, Zunyi; Le Trinh, Thu; Teng, I‐Ting; Wang, Sai; Bradley, Kevin M.; Hoshika, Shuichi; Wu, Qunfeng; Cansiz, Sena; Rowold, Diane J.; McLendon, Christopher; Kim, Myong‐Sang; et al.
Abstract: Laboratory in vitro evolution (LIVE) might deliver DNA aptamers that bind proteins expressed on the surface of cells. In this work, we used cell engineering to place glypican 3 (GPC3), a possible marker for liver cancer theranostics, on the surface of a liver cell line. Libraries were then built from a six‐letter genetic alphabet containing the standard nucleobases and two added nucleobases (2‐amino‐8 H ‐imidazo[1, 2‐ a ][1, 3, 5]triazin‐4‐one and 6‐amino‐5‐nitropyridin‐2‐one), Watson–Crick complements from an artificially expanded genetic information system (AEGIS). With counterselection against non‐engineered cells, eight AEGIS‐containing aptamers were recovered. Five bound selectively to GPC3‐overexpressing cells. This selection–counterselection scheme had acceptable statistics, notwithstanding the possibility that cells engineered to overexpress GPC3 might also express different off‐target proteins. This is the first example of such a combination.